2015
DOI: 10.1523/jneurosci.5122-14.2015
|View full text |Cite
|
Sign up to set email alerts
|

Knock-In Mice with NOP-eGFP Receptors Identify Receptor Cellular and Regional Localization

Abstract: The nociceptin/orphanin FQ (NOP) receptor, the fourth member of the opioid receptor family, is involved in many processes common to the opioid receptors including pain and drug abuse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
67
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(69 citation statements)
references
References 58 publications
2
67
0
Order By: Relevance
“…Recently, knock-in mice have been developed with NOP-eGFP receptors in place of the native receptor (Ozawa et al, 2015), similar to knock-in mice containing delta-eGFP and mu-mCherry receptors (Scherrer et al, 2006;Erbs et al, 2015). For each of these mutant mice, the tagged receptor has been valuable in identifying receptor location and trafficking without the need for problematic opioid receptor antibodies, with resolution far superior to in vitro autoradiography.…”
Section: B Location Of Nociceptin Opioid Peptide Receptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, knock-in mice have been developed with NOP-eGFP receptors in place of the native receptor (Ozawa et al, 2015), similar to knock-in mice containing delta-eGFP and mu-mCherry receptors (Scherrer et al, 2006;Erbs et al, 2015). For each of these mutant mice, the tagged receptor has been valuable in identifying receptor location and trafficking without the need for problematic opioid receptor antibodies, with resolution far superior to in vitro autoradiography.…”
Section: B Location Of Nociceptin Opioid Peptide Receptorsmentioning
confidence: 99%
“…In this regard, new tools being currently developed will soon be available to study NOP receptor circuitry. NOP-eGFP knockin mice have already demonstrated utility in identifying NOP receptor-containing cells in the brain, spinal cord, and DRG (Ozawa et al, 2015).…”
Section: Future Directions and New Toolsmentioning
confidence: 99%
“…In particular, recent efforts using MOR-mCherry, and DOR-eGFP have determined that these receptors are expressed in distinct but overlapping populations dependent on the cell type and location. Furthermore, findings in NOPR-eGFP mice were recently published (91), and it was revealed that this receptor is expressed in a subpopulation of DRG neurons. Additionally, initial and intriguing data were reported on internalization properties of NOPR within endogenous neuronal cultures (91).…”
Section: Rodent Genetic Tools For Dissecting Opioid Receptor Functionmentioning
confidence: 90%
“…Furthermore, findings in NOPR-eGFP mice were recently published (91), and it was revealed that this receptor is expressed in a subpopulation of DRG neurons. Additionally, initial and intriguing data were reported on internalization properties of NOPR within endogenous neuronal cultures (91). These types of receptor-fusion fluorophore approaches do come with caveats, given that the GFP/mCherry tag could interfere with receptor trafficking and function.…”
Section: Rodent Genetic Tools For Dissecting Opioid Receptor Functionmentioning
confidence: 90%
See 1 more Smart Citation